Attitude of the youth in the Republic of Tatarstan towards organ donation - A. A. Anisimov; E. S. Gilmetdinova; M. A. Mulendeeva; A. Yu. Anisimov (Вестник трансплантологии и искусственных органов)
Objective: to study the views of the youth in the Republic of Tatarstan on organ donation and transplantation, to analyze their awareness and ideas about donor transplants and potential their willingness to become organ donors.Materials and methods. An anonymous sociological survey of 880 respondents aged 18 to 35 from the Republic of Tatarstan was conducted in the period from January 1 to July 1, 2021. An 11-question questionnaire was developed using online service Google Forms. Participation in the survey was voluntary.Results. Female and male respondents accounted for 79.0% and 21.0%, respectively; 34.2% of the respondents have or are receiving medical education. Among the respondents, 71.5% have a clear understanding of the term «organ donation», 27.4% are not sure of their understanding, 1.1% do not have a clear understanding. 56.8% consider the issue of organ donation for transplantation in the Republic of Tatarstan as a pressing matter, 3.5% do not see it so, while 39.7% found it difficult to answer. After death, 35.9% would agree to become donors, 39.5% probably would agree, 9.3% probably would disagree, 5.6% strongly disagrees, 9.7% found it difficult to answer. The most common associations with organ donation were positive: 34.5% associate it with «life», 25.1% with «help», and 22.0% with «lifeline».Conclusion. Young people in the Republic of Tatarstan are ready for a healthy debate of the problem of organ donation and most of them see it as a noble course. Given the interest in the problem and lack of awareness by the target audience, it is advisable to include independent academic disciplines on transplantology and organ donation in the curriculums of medical universities in the country. It is necessary to attract modern interdisciplinary information and educational resources to promote organ donation among the Russian public.